Decision Support System Determining Differentiate Learning In Students Using The Moora Method - Agus Sapitri, Liana; Fauzi, Achmad; Simanjuntak, Magdalena (Journal of Engineering, Technology and Computing (JETCom), 2024)
Quick and precise decision-making is key in facing global competition. Based on the results of research conducted at STMIK Kaputama Binjai, the learning process for students is good, but they still have to develop other methods in the learning process. less effective and efficient, not in accordance with differentiated learning. Differentiated learning is learning that gives students the freedom to increase their potential according to their learning readiness, interests, and learning profile. Differentiated learning does not only focus on learning products, but also focuses on processes and content or materials. To overcome this problem, it is necessary to build a system to streamline the process of determining the methods that need to be applied in well-computerized classrooms by utilizing the processes of the Decision Support System (DSS). Based on the results of the research conducted, it was found that the Kinesthetic Learning Model with a value of 0.715; has the highest score and is ranked first. With these results it is also concluded that the learning model is appropriate to be a learning model in providing students with differentiated learning.